Analysis of Impact of Modified Piston - Sucharitha, G.; Rai, Ramesh (International Journal of Psychosocial Rehabilitation, 2019)
The piston is the heart of the engine, and its working condition is the most exceedingly bad one of the key parts of the engine in the workplace. A piston is a segment of responding pistons responding pumps, gas compressors, and pneumatic chambers, among other comparative systems. It is the moving part that is contained by a barrel and is made gastight by piston rings. In a piston, its motivation is to exchange force from growing gas in the barrel to the crankshaft through a piston bar and additionally associating pole connecting rod. The main objective is to investigate and analyze the behavior stress and structural analysis of the modified piston at the real engine condition during the combustion process. This work advances by utilizing finite element analysis to anticipate the higher stress and critical area on the component.